АНТИБИОТИКОРЕЗИСТЕНТНОСТЬ БАКТЕРИАЛЬНЫХ ВОЗБУДИТЕЛЕЙ МАСТИТА КРУПНОГО РОГАТОГО СКОТА В ХОЗЯЙСТВАХ КОСТАНАЙСКОЙ ОБЛАСТИ - Б. Мустафин; В. Сущих; В. Ракецкий; С. Хлюпко; А. Каримов (Animal Health and Biosafety, 2026)
Cattle mastitis is one of the most common and economically significant pathologies of dairy farming, leading to a decrease in productivity, a deterioration in milk quality and an increase in the cost of animal treatment. According to domestic and foreign researchers, the main bacterial pathogens of mastitis are Staphylococcus aureus, streptococci and representatives of the Enterobacteriaceae family, primarily Escherichia coli (1, 4, 8). An important factor limiting the effectiveness of mastitis therapy is the formation of antibiotic resistance of microorganisms due to prolonged and often irrational use of antibacterial drugs (2, 9). The purpose of this study was to study the species composition of microflora and the antibiotic sensitivity profile of microorganisms isolated from cows with mastitis in the farm of Kostanay region. The material for the study was milk samples from cows with clinical forms of mastitis. Bacteriological studies were carried out using standard culture media, the identification of microorganisms was carried out according to morphological, cultural and biochemical characteristics. The antibiotic sensitivity of the isolated cultures was determined by the method of diffusion in agar with the interpretation of the results in accordance with the CLSI recommendations (6). It was found that the main causative agents of mastitis were Staphylococcus aureus, Streptococcus agalactiae and Escherichia coli. A high sensitivity of isolates to fluoroquinolone antibiotics and a reduced sensitivity to β-lactam antibiotics were revealed, which indicates the formation of antibiotic resistance and is consistent with the data of domestic and foreign studies (2, 4, 11).